2010
DOI: 10.1111/j.1469-1795.2010.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of stress hormones in crop-raiding male elephants

Abstract: Crop raiding is one of the most common forms of human-elephant conflict. Deterring elephants from raiding crops requires an understanding of the factors influencing the behavior of the individuals involved. We collected fecal samples from five group ranches in southern Kenya where crop-raiding incidents had occurred (n= 10) and two protected areas, Amboseli National Park (n =24) and Maasai Mara National Reserve (n = 20). We used molecular sexing to sex the individuals and radioimmunoassay kits to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 44 publications
(42 reference statements)
1
28
1
Order By: Relevance
“…In many parts of Africa, managers are concerned with elephants leaving core protected areas and damaging agricultural crops (or crop raiding), a behaviour that in itself can result in elephants entering elevated physiological states (Ahlering et al . ). Our findings suggest that elephants in an elevated physiological state are more likely to use refugia and less likely to make exploratory movements.…”
Section: Discussionmentioning
confidence: 97%
“…In many parts of Africa, managers are concerned with elephants leaving core protected areas and damaging agricultural crops (or crop raiding), a behaviour that in itself can result in elephants entering elevated physiological states (Ahlering et al . ). Our findings suggest that elephants in an elevated physiological state are more likely to use refugia and less likely to make exploratory movements.…”
Section: Discussionmentioning
confidence: 97%
“…African elephants with high stress (fGCM) levels exhibited streaking (rapid unidirectional movement) and refuge behaviours along with restricted and altered habitat preferences (Jachowski et al, 2012(Jachowski et al, , 2013. Ahlering et al (2011a) showed, on the basis of limited sampling, elevated fGCM levels in crop-raiding male African elephants than those in nearby protected areas. Season (dry season as 'D' and wet season as 'W').…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported from Kasungu (Malawi) where high levels of poaching, of mainly bulls, led to additional males continuously moving into the area (Bell ). Younger bulls are more often responsible for crop raiding (Chiyo et al , Ahlering et al ), but the older bulls are required for a good trophy income (Hurt and Ravn , Festa‐Bianchet , Milner et al , Slotow et al ). Regulations on damage causing animals differ between Botswana and South Africa.…”
Section: Discussionmentioning
confidence: 99%